Development of a software product for analyzing the calculation results of elastic properties - Zhykhariev, Vladyslav (National Technical University "Kharkiv Polytechnic Institute", 2025)
The study focuses on the application of a developed software product for analyzing the elastic properties of polycrystalline copper, considering size effects and initial point concentrations. The software’s capabilities in visualization and evaluation of optimal material parameters are demonstrated.
Keywords: software product; numerical modeling; elastic properties; size effect; initial point concentration; histograms; data visualization